Entrapment - dream : novel - Yasar, Mohamed (CreateSpace Independent Publishing Platform, 2017)
"A spiritual young man searches for the meaning of love, and through his journey we see a truth of the world laid out before us. What is true love? What is God's real message?"--Back cover.